Rich pictures for stakeholder dialogue: A polyphonic picture book. (May 2018) - Durrant, Abigail C.; Kirk, David S.; Moncur, Wendy; Orzech, Kathryn M.; Taylor, Robyn; Trujillo Pisanty, Diego
Abstract : We describe the design and use of a 'polyphonic picture book' for engaging stakeholders and research participants with findings from an interdisciplinary project investigating how UK citizens create and manage online identities at three significant life transitions. The project delivered socio-cultural and technical findings to inform policy-making and service innovation for enhancing digital literacy in online self-representation. The picture book presented findings through multi-perspectival, fictional scenarios about experiences of life transition. We describe our use of the book with our stakeholders in five workshop settings and our evaluation of the visual format for fostering stakeholder dialogue around the findings and their transferability. This paper contributes methodological insights about using visual storytelling to scaffold interpretative, dialogical contexts of research engagement. Highlights: A polyphonic picture book promotes stakeholder engagement with design research findings. Character-driven scenarios create interpretative frames for stakeholder understanding. Picture book production involved knowledge exchange in the interdisciplinary team.